The authoritarian practice of issuing internet shutdowns in India: the Bharatiya Janata Party's direct and indirect responsibility. Issue 4 (19th May 2022) - Ruijgrok, Kris
ABSTRACT: This article examines India's troubling rise in internet shutdowns. Focusing on internet shutdowns issued outside of the conflict-prone region of Jammu and Kashmir, the article asks two essential questions: One, who issues the shutdowns in India? And two, why are they issued? Using qualitative fieldwork conducted in two Indian states, and quantitative data analysis of recorded internet shutdowns across the country, the article argues that (1) rather than a centrally coordinated, top-down campaign from the central government, India's 28 state governments are largely responsible for the issuing of shutdowns, and (2) the Hindu-nationalist Bharatiya Janata Party (BJP) is both directly and indirectly responsible for many of India's shutdowns. BJP-run state governments issue more shutdowns than non-BJP states, primarily to suppress protest (the direct responsibility), while the party's polarizing rhetoric and policies, coupled with the BJP-built limited regulatory framework governing the issuance of shutdowns, contribute to an environment in which the shutdowns can thrive (the indirect responsibility). Confirming these arguments, my quantitative analyses (2012–2020) reveal that districts in BJP-ruled states experience significantly more internet shutdowns (primarily in response to protests), while Hindu-Muslim conflict triggers internet shutdowns all across the country.